2009
DOI: 10.1002/chir.20701
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional chromatography method applied to the enantiomeric determination of lansoprazole in human plasma by direct sample injection

Abstract: A two-dimensional HPLC method based on the direct injection of biological samples has been developed and validated for the determination of lansoprazole enantiomers in human plasma. The lansoprazole enantiomers were extracted from the biological matrix using an octyl restricted access media bovine serum albumin column (C8 RAM BSA) and the enantioseparation was performed on an amylose tris(3,5-dimethoxyphenylcarbamate) chiral column using acetonitrile:water (35:65 v/v) and UV detection at 285 nm. Analysis time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…In all cases, reversed‐phase mode of elution was used in the second dimension for the enantioseparation. The complete descriptions of the analytical methods have been previously published 13–15. Briefly, all three methods showed excellent linearity, precision, accuracy, recovery, and limit of quantification for each of the enantiomers, as follow: pantoprazole 0.20 μg/ml, omeprazole 0.05 μg/ml, and lansoprazole 0.10 μg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, reversed‐phase mode of elution was used in the second dimension for the enantioseparation. The complete descriptions of the analytical methods have been previously published 13–15. Briefly, all three methods showed excellent linearity, precision, accuracy, recovery, and limit of quantification for each of the enantiomers, as follow: pantoprazole 0.20 μg/ml, omeprazole 0.05 μg/ml, and lansoprazole 0.10 μg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the plasma concentration of each LAN enantiomer appeared to be influenced by enantioselective metabolism in liver and, by enantioselective protein binding . On the enantioselective pharmacokinetics of LAN, the plasma concentration of (+)‐LAN was higher than (–)‐LAN . Therefore, LAN enantiomers may have different pharmacokinetic properties, pharmacodynamics, and toxicology.…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of HPLC and SFC methods for the determination of LAN enantiomers in biological matrix have been reported . But the selectivity and sensitivity of UV detection has obvious disadvantages compared with MS, the analysis time and the LODs of these methods were not so satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…However, the differences in stereochemical properties of the two enantiomers had pronounced impacts on their pharmacodynamics and pharmacokinetics. As a consequence of the numerous merits of R-(+)-lansoprazole, such as the slower metabolism, higher plasma concentration, longer elimination half-time and greater systemic exposure, it was developed and approved for marketing as a novel proton-pump inhibitor with the trade name Dexilant in 2009 (Gomes, Cassiano, Pedrazzoli, & Cass, 2010;Hershcovici, Jha, & Fass, 2011;Katsuki, Hamada, Nakamura, Arimori, & Nakano, 2001;Metz, Vakily, & Dixit, 2009). In addition, research on the extent of enantioselective binding of lansoprazole enantiomers to human serum proteins demonstrated that R-(+)lansoprazole was more tightly bound to serum proteins than S-(−)lansoprazole (Zhou, Yan, Pan, & Zeng, 2008).…”
Section: Introductionmentioning
confidence: 99%